2012
DOI: 10.1111/mmi.12051
|View full text |Cite
|
Sign up to set email alerts
|

The histone acetyltransferase Hat1 facilitates DNA damage repair and morphogenesis in Candida albicans

Abstract: SummaryChromatin assembly and remodelling is an important process during the repair of DNA damage in eukaryotic cells. Although newly synthesized histone H4 is acetylated prior to nuclear import and incorporation into chromatin during DNA damage repair, the precise role of acetylation in this process is poorly understood. Here, we identify the histone acetyltransferase 1 (Hat1) catalysing the conserved acetylation pattern of histone H4 preceding its chromatin deposition in the fungal pathogen Candida albicans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 106 publications
4
63
0
4
Order By: Relevance
“…These observations agree with our suggestion that impairment of an early step on HR or Cse4 deposition/kinetochore assembly triggers growth polarization in C. albicans (Mitra et al, 2014). Filamentation of deletants in histone modifiers hat1 and rtt109 could also be explained by defects in DNA repair or impairment on putative Cse4 modifications which could be needed for its deposition at centromeres (Lopes da Rosa et al, 2010;Mitra et al, 2014;Tscherner et al, 2012). On the contrary, a C. albicans mec1 null mutant, which is impaired in the detection of DNA damage that triggers the DNAdamage checkpoint, is only poorly filamentous (Legrand et al, 2011).…”
Section: On the Cellular And Molecular Bases Of Rad51 And Rad52 Filamsupporting
confidence: 87%
See 1 more Smart Citation
“…These observations agree with our suggestion that impairment of an early step on HR or Cse4 deposition/kinetochore assembly triggers growth polarization in C. albicans (Mitra et al, 2014). Filamentation of deletants in histone modifiers hat1 and rtt109 could also be explained by defects in DNA repair or impairment on putative Cse4 modifications which could be needed for its deposition at centromeres (Lopes da Rosa et al, 2010;Mitra et al, 2014;Tscherner et al, 2012). On the contrary, a C. albicans mec1 null mutant, which is impaired in the detection of DNA damage that triggers the DNAdamage checkpoint, is only poorly filamentous (Legrand et al, 2011).…”
Section: On the Cellular And Molecular Bases Of Rad51 And Rad52 Filamsupporting
confidence: 87%
“…Growth polarization has also been reported in strains deficient in DNA repair. These include deletion mutants lacking homologous recombination (HR) genes (RAD52, RAD51, and RAD54), exonucleases genes (RAD50 and MRE11) involved in resection of double strand breaks to generate ssDNA, the substrate for Rad51 binding (Andaluz et al, 2006;Hoot et al, 2011;Legrand et al, 2007), or chromatin-modifying genes, such as RTT109 or HAT1 (Lopes da Rosa et al, 2010;Tscherner et al, 2012). Growth polarization in response to genotoxins appears to be mediated by both the DNA-replication and DNAdamage checkpoint pathways, since deletion of effector kinase RAD53 abolishes filamentation (Loll-Krippleber et al, 2014;Shi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that this protein might act in concert with Rpd3 to regulate W/O switching. Although sequence comparisons indicated some similarities of orf19.7185 to the acetyltransferase subunit Hat2 of S. cerevisiae (34), the alignment revealed a high conservation with ScUme1 (Fig. 4C).…”
Section: Resultsmentioning
confidence: 99%
“…All deletion cassettes were constructed by fusion PCR (51) with a fragment containing the selection marker fused to the corresponding upstream and downstream region. Deletion of orf19.7185 in strain J4-2.1 was performed using the linearized plasmid pSFS2A-Ca7185 after digestion with PvuII (34). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation